Development of Sorghum Flour not Passing Sieve as Fried Chicken Flour with Pregelatinization Technique - Alfatah, Reza Fikri; Faturochman, Hadi Yusuf; Nur’alina, Ina; Salsabila, Tsania Nashiroh (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2024)
Sorghum flour that not passing sieve can be reused effectively as an ingredient for fried chicken seasoning flouur. To achieve the desired quality, it must be modification, and one of the effective methods for modification is through the flour pre-gelatinization process before use. This research aims to improve the characteristics of sorghum flour that not passing sieve by applying the pre-gelatinization process to produce good fried chicken seasoning flour. Subsequently, a completely randomized design (CRD) was used with two treatments, namely sorghum flour that not passing sieve without going through a pre-gelatinization process, and sorghum flour that not passing sieve that had been pre-gelatinized. The pre-gelatinization process is able to change the physical characteristics of the resulting flour which is characterized by an increase in peak viscosity (PV) of 1310.25 cP and trough viscosity (TV) of 374.50 cP. Similarly, there was a decreased in breakdown viscosity (BD) was 198.50 cP, the final viscosity (FV) was 2174.25 cP, and the setback viscosity (SB) was 2148.75 cP. The paste temperature was 74.39 °C, while the peak gelatinization time (peak time in minutes) remained unchanged at 7.00 minutes and was able to increase the water absorption capacity to 195.75%. The use of pre-gelatinized sorghum flour that not passing sieve in fried chicken flour can produce seasoned flour with a crunchy texture and high friability value, has a favorable value for the attributes of color and good appearance. The proximate analysis of fried chicken flour, it shows that pregelatinization treatment of sorghum flour can cause a significant decrease in protein content of up to 7.99% and a significant increase in water content of up to 11.27%. The research results show that pregelatinized sorghum flour improves its characteristics so that it becomes the right choice for developing fried chicken flour products.